2017
DOI: 10.1103/physreve.95.062107
|View full text |Cite
|
Sign up to set email alerts
|

Geometric structure and information change in phase transitions

Abstract: We propose a toy model for a cyclic order-disorder transition and introduce a geometric methodology to understand stochastic processes involved in transitions. Specifically, our model consists of a pair of forward and backward processes (FPs and BPs) for the emergence and disappearance of a structure in a stochastic environment. We calculate time-dependent probability density functions (PDFs) and the information length L, which is the total number of different states that a system undergoes during the transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(94 citation statements)
references
References 55 publications
5
85
2
Order By: Relevance
“…Of course, Z → ∞ cannot be achieved in any numerical solver; some finite upper boundary must always be chosen. In previous work on other Fokker-Planck equations [35,36], the resulting PDFs dropped off sufficiently rapidly for large z (exponentially or even faster) that just imposing p(Z) = 0 yielded excellent results, and conserved the total probability extremely well. Here though this approach was found not to work, and caused the integral Z 0 p dz to decrease in time, even if Z as large as 100 was chosen.…”
Section: A Logistic Stationary Distributionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of course, Z → ∞ cannot be achieved in any numerical solver; some finite upper boundary must always be chosen. In previous work on other Fokker-Planck equations [35,36], the resulting PDFs dropped off sufficiently rapidly for large z (exponentially or even faster) that just imposing p(Z) = 0 yielded excellent results, and conserved the total probability extremely well. Here though this approach was found not to work, and caused the integral Z 0 p dz to decrease in time, even if Z as large as 100 was chosen.…”
Section: A Logistic Stationary Distributionmentioning
confidence: 99%
“…[39,40]), our recent work [27,28,[33][34][35][36] adapted this concept to a non-equilibrium system to elucidate geometric structure of non-equilibrium processes. Specifically, [35] mapped out the attractor structure L ∞ vs z 0 for linear and cubic processes and showed that a linear damping preserves a linear geometry L ∞ ∝ z 0 whereas a nonlinear damping gives rise to a power-law scaling L ∞ ∝ z n 0 (n ∼ 1.5 − 1.9) of the attractor structure. [28] found interesting geodesic solutions in a non-autonomous Ornstein-Uhlenbeck (O-U) process [32] by modulating model parameters and by including time-dependent external deterministic killing term.…”
Section: Information Lengthmentioning
confidence: 99%
See 3 more Smart Citations